Project report on N:1 Modem Switch over Unit - AJMAL AHMED, ROHIT SUDHIR and BISWADIP CHAKRABORTHY (2004)
INTERNAL GUIDE: R N MANJULA, MVJCE EXTERNAL GUIDE: SATISH MOREY, ITI MANAGER
Keywords: Modem Switch over Unit